Orchids in Rolpa district of Western Nepal: Documentation, stock, trade and conservation - Koirala, PN; Pyakurel, D; Gurung, K (Banko Janakari, 2011)
Orchids are perennial, epiphytic, terrestrial or lithophytic herbs with roots having multilayered spongy tissues. In Nepal, 363 species of orchids are organized into 97 genera. Orchids fall under the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) Appendix II but do not fall under the legal protection of any existing national legislation. Habitat loss, forest destruction and degradation and over-exploitation have posed threats to the conservation of orchids in Nepal. The current study aims to document the orchids and estimate the stock of Dendrobium denudans and Dendrobium eriiflorum in a few potential locations of Rolpa district. A total of 36 species were documented in the surveyed 17 Village Development Committees (VDCs). Among them, 31 species were identified up to species level, two species up to generic level and the remaining three were unidentifed. The total stock of D. denudans was highest in Uwa VDC with 11018.08 kg followed by Seram VDC with the stock of 9982.57 kg. Similarly, D. eriiflorum stock in Seram, Siuri and Jaimakasala VDCs were 22750.01 kg, 7039.67 kg and 4933.46 kg, respectively. This study recommends a systematic research on the propagation technique; complete indexing of orchids; and inclusion of orchids in the Red Data Book on the threatened and endangered species. Orchid reserves in orchid hotspots should be established for the preservation and promotion of regeneration activities. The rare and endangered species should be preserved in botanic gardens. In addition to scientific attempts, the country should launch and implement a very firm regulation for their protection. Key words: Orchids; Dendrobium denudans; Dendrobium eriiflorum; distribution; conservation; Rolpa district DOI: 10.3126/banko.v20i2.4796 Banko Janakari Vol.20(2) 2010 pp.3-13